ChemInform Abstract: Calix[n]arenes: Active Organocatalysts for the Synthesis of Densely Functionalized Piperidines by One‐Pot Multicomponent Procedure. Issue 35 (August 2016) - Palermo, V.; Sathicq, A.; Liberto, N.; Fernandes, S.; Langer, P.; Jios, J.; Romanelli, G.
Abstract: The reaction provides functionalized piperidines with high anti‐selectivity.